Implications of Online Learning: Trends of Science Misconceptions about Forces in Elementary School - Munastiwi, E.; Saputro, B.; Fatonah, S.; Suhendro, E. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
This study aims to understand the tendency of science misconceptions about